THE TRICKING OF ADVERTISERS (Critical Pragmatic Analysis) - Tomson Sabungan Silalahi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT Advertisements have their ideologies, values and particular interests existing in them and that must be viewed critically. Using critical pragmatic analysis, this article aims to unravel critically the ideologies, values and interests that advertisers want to convey through the discourse they conceal. To dismantle it, we will take such steps; (1) transcribing data from spoken language into written language, (2) noting how the overall narrative of the visual organization and the text in the advertisement; (3) examines imagery to be built by the advertiser, how the advertiser's imaging process is represented, who is omitted/ignored by the advertisement, what is ignored or absent in the advertisement, and last (4) the establishment of a text link; assessment, representation, relationships, identification. The results were obtained as follows; Ramayana Department Store (RDS) wants to change the mindset of its audience about the word “cool”. Implicitly viewers are forced to become more consumptive. If it should be likened to film, then advertiser act as protagonist, parents as antagonist and children as object which is oppressed. Keywords: Ramayana Department Store, critical pragmatics, advertisement